2020
DOI: 10.1158/1535-7163.mct-20-0550
|View full text |Cite
|
Sign up to set email alerts
|

Selective Vulnerability to Pyrimidine Starvation in Hematologic Malignancies Revealed by AG-636, a Novel Clinical-Stage Inhibitor of Dihydroorotate Dehydrogenase

Abstract: ◥Agents targeting metabolic pathways form the backbone of standard oncology treatments, though a better understanding of differential metabolic dependencies could instruct more rationale-based therapeutic approaches. We performed a chemical biology screen that revealed a strong enrichment in sensitivity to a novel dihydroorotate dehydrogenase (DHODH) inhibitor, AG-636, in cancer cell lines of hematologic versus solid tumor origin. Differential AG-636 activity translated to the in vivo setting, with complete tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…On the basis of these results, more potent inhibitors of DHODH are being developed for treatment of rheumatoid arthritis and SARS-CoV-2 (ReF. 205 ) as well as cancer [206][207][208] . Another DHODH inhib itor, AG-636 (ReF.…”
Section: ();mentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these results, more potent inhibitors of DHODH are being developed for treatment of rheumatoid arthritis and SARS-CoV-2 (ReF. 205 ) as well as cancer [206][207][208] . Another DHODH inhib itor, AG-636 (ReF.…”
Section: ();mentioning
confidence: 99%
“…Another DHODH inhib itor, AG-636 (ReF. 208 ), with a 17 nM IC 50 , has activity against tumour growth in xenograft models of diffuse large B cell lymphoma (OCILY19), and mantlecell lymphoma (Z138), but limited activity in models of lung (A549) and colon (HCT-116) cancer 208 . Notably, DHODH function is intimately coupled to the mitochondrial ETC for ubiquinone-mediated oxidation of dihydroorotate to orotate 209 .…”
Section: ();mentioning
confidence: 99%
“…The discovery linking pyrimidine starvation to cell fate in AML has reinvigorated interest in DHODH as an anti-cancer target and has spurred extensive efforts to develop more potent and selective next-generation inhibitors [7][8][9][10][11] . In agreement with previous studies, we found that DHODH inhibition has excellent potency in different AML sub-types in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Leflunomide and another DHODHi, brequinar, have been trialed in various cancers and although occasional durable responses were observed, the initial data was insufficient to support further clinical development [3][4][5] . Notably however, recent findings suggesting selective efficacy of DHODHi in hematological malignancies have prompted renewed interest in DHODH as an anti-cancer target and have spurred extensive efforts to develop more potent and selective next-generation inhibitors [7][8][9][10][11] . Intriguingly, AML cells have been reported to undergo myeloid maturation in response to pyrimidine starvation [7][8][9][10] , suggesting a link between nutrient availability and cell fate that can be exploited as a form of "differentiation therapy".…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation